STUDI POPULASI KERANG Contradens contradens (Lea, 1838) YANG TERDAPAT DI DANAU SINGKARAK KABUPATEN SOLOK - Ramanda, Riri - (Pendidikan Biologi, 2014)
Lake is a body of calm waters and habitats of living organisms or aquatic biota. One such organism is the mussel in the family Unionidae Contradens contradens contained in Solok Regency Lake Singkarak. The shells are often captured and used by residents as a source of animal protein for food and livelihood. Arrest shells were constantly threatening the existence of this mussel population extinction even. This study aims to determine the population density and size distribution of mussel shells Contradens contradens and physico-chemical factors of water in Lake Singkarak. This research was conducted in April-May 2014 in Solok Regency Lake Singkarak. Collecting shellfish samples was performed with a Sauah (anchor). Measurement and verification sampling conducted in the Laboratory of Animal Ecology Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. This study used a descriptive survey method using purposive sampling to define four different research stations namely Nagari Tikalak, Singkarak, Saniang Bakar and Muaro Pingai. The results of the measurement and verification samples obtained Contradens contradens shells with an average population density is highest at Station I ranged 11.21 ind/m2 and the lowest ranges from 1.28 ind/m2 at Station II. The average density ranges from 7.67 ind/m2. The ratio of length : Height : Thickness is 1 : 1 : 1, there is a very close correlation between the length, height and thickness with a dry weight of meat. Mussel shell length ranged from 2.7 to 5.5 cm. Distribution of shell length at Station I and IV predominantly young individuals as well as on Station II only adult individuals.